(untitled) (Agro Productividad, 2024)
Objective: to design an interpretive trail of native orchids in the gardens of Campus Cordoba, Colegio de Postgraduados. Design/Methodology/Approach: this study is descriptive and field based. First, the feasibility of the trail was validated through an online survey. Afterwards, several field trips were conducted; the script was created, and finally the interpretive script of the trail was validated. Results: of the respondents, 95% considered the orchid interpretive trail as feasible. The inventory of the trail area allowed to verify that the orchids are accessible at all stations along the route. The design of the interpretive trail has nine thematic stations: 0. Introduction, 1. The Catasetum trail, 2. In vitro germination, 3. Acclimatization of orchids, 4. Miniature orchids, 5. Establishing orchids in phorophytes, 6. The Laelias trail, 7. The “May Flowers” trail, and 8. The “Donkey ears” (Thricocentrum luridum). The interpretive trail allows anyone to know and appreciate the diversity of wild orchids, 28 species and their phorophytes, along 700 m of walking trails for a 2.5-hours route. Limitations of the study/Implications: it is a guided interpretive trail. Findings/Conclusions: The interpretive trail allows us to appreciate the importance of the Orchidaceae family; which is one of the largest families in Mexico and the world through environmental and ornamental importance.